1998
DOI: 10.1002/(sici)1097-0231(19980831)12:16<1045::aid-rcm281>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Apolipoprotein E by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry

Abstract: The genotyping of the various isoforms of Apolipoprotein E (apo E) has been performed using matrix-assisted laser desorption/ionization (MALDI-MS). The polymerase chain reaction was used to amplify the specific apo E gene sequence followed by digestion with Cfo I (Clostridium formicoaceticum), for generating restriction fragments for rapid and accurate mass analysis. An exonuclease I digestion step was introduced to remove the unused primers after PCR, which can otherwise interfere in the mass spectral analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…PCR-RFLP analysis (Zivelin et al, 1997) by means of digestion of the fragment of the coding region of APOE with HhaI is an inexpensive, but error-prone method, due to possible incomplete restriction enzyme digestion or star activity that difficult the interpretation of results. Reverse Hybridization, as well as other methods recently developed, including capillary electrophoresis (Somsen et al, 2002), PCR plus sequencing or mass spectrometry (Srinivasan et al, 1998), and ARMS-PCR (Donohoe et al, 1999), are valuable and convenient techniques for small-scale investigators, but difficult to scale-up for large number of samples. Ponchel et al (2003) proposed the use of SYBR ® Green to perform relative quantification of gene rearrangements, gene amplifications and microgene deletions analysis as alternative to the TaqMan ® methodology (Koch et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR-RFLP analysis (Zivelin et al, 1997) by means of digestion of the fragment of the coding region of APOE with HhaI is an inexpensive, but error-prone method, due to possible incomplete restriction enzyme digestion or star activity that difficult the interpretation of results. Reverse Hybridization, as well as other methods recently developed, including capillary electrophoresis (Somsen et al, 2002), PCR plus sequencing or mass spectrometry (Srinivasan et al, 1998), and ARMS-PCR (Donohoe et al, 1999), are valuable and convenient techniques for small-scale investigators, but difficult to scale-up for large number of samples. Ponchel et al (2003) proposed the use of SYBR ® Green to perform relative quantification of gene rearrangements, gene amplifications and microgene deletions analysis as alternative to the TaqMan ® methodology (Koch et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is a timeconsuming and error-prone method, due to possible incomplete restriction enzyme digestion. Capillary electrophoresis (Somsen et al, 2002), PCR plus sequencing or mass spectrometry (Srinivasan et al, 1998) are effective methods, but require expensive dedicated instrumentation. The ARMS-PCR (Amplification Refractory Mutation System-PCR) (Donohoe et al, 1999) and SSP-PCR (Simple Sequence Specific Primer-PCR) (Pantelidis et al, 2003) methodologies require analysis by agarose gels, thus limiting the number of samples that can be examined at a time.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have shown that MALDI‐MS can be used for rapid and accurate analysis of PCR products (Berkenkamp et al, ; Hurst et al, ; Jurinke et al, ,b; Srinivasan et al, ), although ESI‐MS is often more appropriate for larger PCR products as discussed in UNIT . Satisfactory MALDI‐MS analysis of nucleic acids requires efficient and effective sample purification.…”
Section: Typical Applications Of Maldi‐ms In Oligonucleotide Analysismentioning
confidence: 99%
“…Then, following a simple procedure of purification including phenol extraction and ethanol precipitation, the product is analyzed by MALDI/TOF-MS. 1,5,6 Alternatively, mutations can be identified by measuring restriction enzyme-digested DNA fragments, in a similar way to restriction fragment length polymorphism analysis using gel electrophoresis. 2,3,10 Expansion of trinucleotide repeats has been identified in several genes as the cause of different neurological disorders. 11 -14 In normal individuals, the length of the repeats is usually polymorphic, and the repeats are known to be mildly elongated before transmission to the affected offspring.…”
Section: Introductionmentioning
confidence: 99%